The snRNP core assembly pathway: identification of stable core protein heteromeric complexes and an snRNP subcore particle in vitro. - Raker, V A (1996)
Stable association of the eight common Sm proteins with U1, U2, U4 or U5 snRNA to produce a spliceosomal snRNP core structure is required for snRNP biogenesis, including cap hypermethylation and nuclear transport. Here, the assembly of snRNP core particles was investigated in vitro using both native HeLa and in vitro generated Sm proteins. Several RNA-free, heteromeric protein complexes were identified, including E.F.G, B/B'.D3 and D1.D2.E.F.G. While the E.F.G complex alone did not stably bind to U1 snRNA, these proteins together with D1 and D2 were necessary and sufficient to form a stable U1 snRNP subcore particle. The subcore could be chased into a core particle by the subsequent addition of the B/B'.D3 protein complex even in the presence of free competitor U1 snRNA. Trimethylation of U1 snRNA's 5' cap, while not observed for the subcore, occurred in the stepwise-assembled U1 snRNP core particle, providing evidence for the involvement of the B/B' and D3 proteins in the hypermethylation reaction. Taken together, these results suggest that the various protein heterooligomers, as well as the snRNP subcore particle, are functional intermediates in the snRNP core assembly pathway.